A computational micromechanics approach to evaluate elastic properties of composites with fiber-matrix interface damage. (15th October 2016) - Barulich, Néstor Darío; Godoy, Luis Augusto; Dardati, Patricia Mónica
Abstract: Computational micro-mechanics is employed in this work to evaluate effects of fiber-matrix interface damage on the elastic properties of polymer matrix composites with continuous glass fibers. It is assumed that damage affects local zones along the fiber and a sector on the perimeter around the fiber. Elastic modulii are evaluated using Finite Element analysis, for a range of values in damage parameters considered. The occurrence of bi-modular behavior, with differences in Young's modulus under tension and compression, has been represented by contact without friction. Based on extensive parametric results, a Least Squares Method is employed to derive analytical expressions for each material property as a function of damage parameters. In most cases the elastic modulus has a nonlinear relation with the damage parameter in the length of the fiber, with the exception of the transverse elastic modulus under tension. The analytical expressions are used to couple micro and macro scales in an off-line scheme, without the need to perform in-time micro-scale computations.